Sustainability insights from the mission statements of leading Brazilian Universities - Deus, Rafael Mattos [UNESP]; Gomes Battistelle, Rosane Aparecida [UNESP]; Ribeiro da Silva, Gustavo Henrique [UNESP] (Emerald Group Publishing Ltd, 2016)
Purpose - The purpose of this paper is to investigate the mission statements from 30 leading Brazilian universities, evaluating the statements based on a sustainable model that involves an environmental management system, public participation and social responsibility, and sustainable education and research. Design/methodology/approach - Content analysis was conducted on the mission statements. The points used were based on the campus sustainability model of Alshuwaikhat and Abubakar. After grading, the Pearson correlation was verified for indicator and ranking points. Findings - The authors find few universities with clear sustainability aspects in their mission statements; just 10 percent of institutions achieve five points out of a maximum of nine points. Research limitations/implications - This study analyses only mission statements, which do not provide substantiated real sustainable action as much as reporting does. Practical implications - Higher education managers should review the universities' mission statements in terms of a sustainability overview and improve the statements. Social implications - The authors criticize the real mission stated by leading Brazilian universities and their true role in society. Originality/value - Studies frequently focus on reporting and this work instead focusses on mission statements, which are important for guiding reporting and acting as a strategic tool. The results highlight aspects that have only been rarely addressed by Brazilian universities.
Keywords: Sustainability; Social responsibility; Mission statement; Higher education; Environmental management; Indicators